Uncertainty, Waiting Time, and Capacity Utilization: A Stochastic Theory of Product Quality - De Vany, Arthur (Journal of Political Economy, 1976)
The behavior of a monopoly is analyzed in the following setting. Search creates a stochastic stream of customers. Searchers observe the queue and leave if it is too long. Production is random. In the optimal solution, waiting time, effective demand, and the utilization of capacity are jointly determined. Product quality in the form of waiting time is endogenous to the model, and it is found that price or capacity changes affect both the quantity and the quality of output. If an equilibrium exists, there is excess capacity. Price equals marginal cost, but monopoly produces too little capacity and output unless profits are zero.